3D 7Li magnetic resonance imaging of brain lithium distribution in bipolar disorder. Issue 11 (November 2018) - Smith, Fiona; Thelwall, Peter; Necus, Joe; Flowers, Carly; Blamire, Andrew; Cousins, David
Abstract Lithium is a major treatment for bipolar disorder and the likelihood of a favourable response may be determined by its distribution in the brain. Lithium can be directly detected by magnetic resonance (MR), but previous7 Li MR spectroscopy studies have demonstrated that this is challenging compared to conventional1 H MR imaging due to the MR properties of the lithium nucleus and its low concentration in brain tissue, as dictated by therapeutic dose. We have tested and implemented a highly efficient balanced steady-state free precession7 Li-MRI method to address these challenges and enable MRI of brain lithium in a short duration scan. We report a 3D7 Li-MRI acquisition with 25 mm isotropic resolution in an 8-min scan that demonstrates heterogeneity in lithium concentration within the brain in subjects with bipolar disorder. This represents the direct imaging of a pharmaceutical agent in its target organ and notably expands the repertoire of techniques available to investigate the effects of lithium in man.